(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Effect of seed treatment on seedling health of chili (BARI Morich 1) was studied at Bangladesh Agricultural University (BAU), Mymensingh, Bangladesh. BAU Bio-fungicide (3% of seed weight), chitosan (1% solution), thiovit (0.3% of seed weight), compressed moist heat (54ºC for 15 minutes), neem leaf extract (1:1 w/v), garlic clove extract (1:3 w/v), ginger extract (1:2 w/v) and allamonda leaf extract (1:1 w/v) were employed as seed treating agents. The treated seeds were placed on moistened blotter paper. Data were recorded on percent germination, production of percent healthy seedling and seedling vigour of chili. The results of seed health testing showed that, five different seed borne fungi viz. Colletotrichum capsici, Curvularia lunata, Rhizopus stolonifer, Aspergillus flavus and Fusarium moniliforme were found to be associated with the tested chili seed samples. Among these fungi, Curvularia lunata was the most prevalent one which was followed by Rhizopus stolonifer, Colletotrichum capsici, Fusarium moniliforme and Aspergillus flavus. All the seed treating agents were found to be effective compared to control in controlling seed borne fungi for the blotter method. The highest percentage of germination (93.33%) was recorded when the seeds of BARI Morich 1 were treated with BAU Bio-fungicide, whereas the lowest percentage of germination (61.33%) was recorded in case of untreated seeds. The highest percentage of healthy seedling (95.33%) was recorded when the seeds were treated with BAU Bio-fungicide and allamonda leaf extracts, whereas the lowest percentage of healthy seedling (59.00%) was recorded in case of untreated seeds. The highest vigour index (681.59) was recorded when the seeds were treated with neem leaf extracts, whereas the lowest vigour index (214.66) was recorded in case of untreated seeds. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22167 J. Environ. Sci. & Natural Resources, 7(1): 177-181 2014